Cost‐effectiveness of diagnostic testing strategies including cervical‐length measurement and fibronectin testing in women with symptoms of preterm labor. (30th March 2018) - van Baaren, G.‐J.; Vis, J. Y.; Wilms, F. F.; Oudijk, M. A.; Kwee, A.; Porath, M. M.; Scheepers, H. C. J.; Spaanderman, M. E. A.; Bloemenkamp, K. W. M.; Haak, M. C.; Bax, C. J.; Cornette, J. M. J.; et al.
ABSTRACT: Objective: To evaluate the cost‐effectiveness of combining cervical‐length (CL) measurement and fetal fibronectin (fFN) testing in women with symptoms of preterm labor between 24 and 34 weeks' gestation. Methods: This was a model‐based cost‐effectiveness analysis evaluating seven test–treatment strategies based on CL measurement and/or fFN testing in women with symptoms of preterm labor from a societal perspective, in which neonatal outcomes and costs were weighted. Estimates of disease prevalence, test accuracy and costs were based on two recently performed nationwide cohort studies in The Netherlands. Results: Strategies using fFN testing and CL measurement separately to predict preterm delivery are associated with higher costs and incidence of adverse neonatal outcomes compared with strategies that combine both tests. Additional fFN testing when CL is 15–30 mm was considered cost effective, leading to a cost saving of €3919 per woman when compared with a treat‐all strategy, with a small deterioration in neonatal health outcomes, namely one additional perinatal death and 21 adverse outcomes per 10 000 women with signs of preterm labor (incremental cost‐effectiveness ratios €39 million and €1.9 million, respectively). Implementing this strategy in The Netherlands, a country with about 180 000 deliveries annually, could lead to an annual cost saving of between €2.4 million and €7.6 million, with only a small deterioration in neonatal health outcomes. Conclusion: In women with symptoms of preterm labor at 24–34 weeks' gestation, performing additional fFN testing when CL is between 15 and 30 mm is a viable and cost‐saving strategy. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.